(untitled) - Uys, Janien

Ruminal and intestinal digestibility of rumen protected lysine and its effect on production responses in Merino rams (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.